Functional genomics of Familial Hypercholesterolemia - Alves, Ana Catarina (2016)
Main aim of the Portuguese Family Hypercholesterolemia study: to identify the cause of the dyslipidaemia in patients with a clinical phenotype of Familial Hypercholesterolaemia (FH).